STRATEGI GURU DALAM MENGEMBANGKAN SOSIAL EMOSIONAL ANAK DI TAMAN KANAK-KANAK - Umil Lasmita; Fiqi Nurmanda Sari; Anisah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social-emotional development is one of the key aspects that must be nurtured from an early age, as it plays a role in shaping a child’s ability to interact, collaborate, manage emotions, and adapt to their environment. Based on preliminary observations at Harapan Ibu Kindergarten in Ngaol Village, Tabir Barat Subdistrict, Merangin Regency, some children were still found to be unable to control their emotions, lacked self-confidence, and had difficulty interacting with their peers. This study aims to describe teachers’ strategies for fostering children’s social-emotional development, assess the current state of children’s social-emotional development, and identify factors that support and hinder the implementation of these strategies. The study employed a qualitative approach using a descriptive research design. The research subjects consisted of the principal, teachers, and children aged 4–6 years. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques, with validity tested through triangulation. The results showed that teachers implemented these strategies through role-playing, modeling positive behaviors, setting a good example, group activities, and warm communication with the children. These strategies were effective in improving the children’s ability to cooperate, share, help peers, regulate their emotions, and interact positively. Supporting factors include cooperation between teachers and parents, a conducive school environment, and the availability of engaging play activities, while inhibiting factors include differences in children’s personalities, a lack of parental attention, and limited learning resources. Thus, the implementation of teachers’ strategies through role-playing and positive reinforcement has been proven to optimally support children’s social-emotional development